Emotional routes in families of victims of harassment: case study in school of risk area - Rubén García Cruz; Citlali Hernández Sánchez (INFAD, 2019)
The present investigation is of mixed type, based on case study, which was divided into two phases, the first exploratory-descriptive type whose objective was to describe the phenomenon of harassmentvictimization through the ERAVE Scale, composed of three subscales, in infants enrolled in a risk  zone at “Margarita Maza de Juárez” Elementary, San Agustín Tlaxiaca, Hidalgo, which was applied to 38 students. The second with an ethnographic educational approach, whose purpose was to analyze the discourses obtained through the semi-structured interview in 3 schoolchildren with high scores on the victimization scale, these allowed to deepen the family and socio-cultural reality of the infants and their behavior in school. The results indicate that the higher the quality of emotional routines in the family, the lower the probability that they are immersed in the harassmentvictimization phenomenon, manifesting normal levels of anxiety and anguish. The study subjects are immersed in a violent family dynamic. Thus, emotional routines are little systematized and superficial ties in these families. When based on positive emotions, they enhance protective factors that favor resilience and mental health.